The Quest for System-Theoretical Medicine in the COVID-19 Era - Tretter, Felix; Wolkenhauer, Olaf; Meyer-Hermann, Michael; Dietrich, Johannes W.; Green, Sara; Marcum, James; Weckwerth, Wolfram (Frontiers in Medicine, 2021)
Precision medicine and molecular systems medicine (MSM) are highly utilized and successful approaches to improve understanding, diagnosis and treatment of many diseases from bench-to-bedside. Especially, in the COVID-19 pandemic molecular techniques and biotechnological innovation have proven to be of utmost importance for rapid developments in disease diagnostics and treatment, including DNA and RNA sequencing technology, treatment with drugs and natural products and vaccine development. The COVID-19 crisis, however, has also demonstrated the need for systemic thinking and transdisciplinarity, and the limits of MSM: the neglect of the bio-psycho-social systemic nature of humans and their context as the object of individual therapeutic and population-oriented interventions. COVID-19 illustrates how a medical problem requires a transdisciplinary approach in epidemiology, pathology, internal medicine, public health, environmental medicine and socio-economic modelling. Regarding the need for conceptual integration of these different kinds of knowledge we suggest the application of general systems theory (GST). This approach endorses an organism-centered view on health and disease, which according to Ludwig von Bertalanffy as one of the founders of GST, we call Organismal Systems medicine (OSM). We argue that systems science offers wider applications in the field of pathology and can contribute to an integrative systems medicine by (i) integration of evidence across functional and structural differentially scaled subsystems, (ii) conceptualization of complex multilevel systems, and (iii) suggesting mechanisms and nonlinear relationships underlying the observed phenomena. We underline these points with a proposal on multi-level systems pathology including neurophysiology, endocrinology, immune system, genetics and general metabolism. An integration of these areas is necessary to understand excess mortality rates and polypharmacological treatments. In the pandemic era this multi-level systems pathology is most important to assess potential vaccines, their effectiveness, short- and long-time adverse effects . We further argue that these conceptual frameworks are not only valid in the COVID-19 era but important to be integrated in a medicinal curriculum.